2016
DOI: 10.14254/1800-5845.2016/12-3/4
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Approach to Estimates Entropy and Risks for Innovative Projects and Programs

Abstract: The article deals with the development and implementation of innovative development programs as an ordered sequence of decisionmaking. Innovations are considered as a specific form of chaos or disorder in the transition to a new level of development. As known, innovative projects have a high level of internal and external uncertainties. Therefore they are difficult for evaluated using classical mathematical methods. In this case authors proposed to use fuzzy entropy for the selection of innovative projects. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…Осылайша жүргізілген зерттеу Қазақстанның технологиялық әлеуетін жан-жақты сипаттайды, ең маңыздысы Қазақстан алдағы уақытта технологиялық жаңғыру арқылы жоғары технологиялы өндірісін дамытып, экпортты әртараптандыру қажет, сол арқылы экономикалық өсімді тұрақты қамтамасыз етуге әлеуеті жоғары болады. етеді [16].Өсуді және сапалы заманауи үлгілерді қолдана отырып әлемдік нарықтағы бәсекеге қабілеттілікті арттыруға қол жеткізу бүгінгі күннің талабы. Ол өндіріске жаңа технологияларды енгізумен және ғылыми сыйымды экономиканың дамуымен тікелей байланысты.…”
Section: әдебиеттерге шолуunclassified
“…Осылайша жүргізілген зерттеу Қазақстанның технологиялық әлеуетін жан-жақты сипаттайды, ең маңыздысы Қазақстан алдағы уақытта технологиялық жаңғыру арқылы жоғары технологиялы өндірісін дамытып, экпортты әртараптандыру қажет, сол арқылы экономикалық өсімді тұрақты қамтамасыз етуге әлеуеті жоғары болады. етеді [16].Өсуді және сапалы заманауи үлгілерді қолдана отырып әлемдік нарықтағы бәсекеге қабілеттілікті арттыруға қол жеткізу бүгінгі күннің талабы. Ол өндіріске жаңа технологияларды енгізумен және ғылыми сыйымды экономиканың дамуымен тікелей байланысты.…”
Section: әдебиеттерге шолуunclassified
“…Innovation is understood as the result of interaction between various economic and social processes (Manley, 2003). Studies published in the last decade showed that innovation is the engine of the growth, being an important element of the development achievements (Szabo, Šoltés, & Herman, 2013;Chernov, Dorokhova & Dorokhov, 2016). Innovation activities play an important role in economic growth and can be considered as the engine of sustainable development of economies (Juřičková & Novák, 2015;Belás & Gabčová, 2016;Rosha & Lace, 2015;Čirjevskis, 2016;Tvaronavičienė, 2017;Tetsman et al, 2017;Oganisjana et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Innovative process is consistently performed in spheres of science, equipment, production and consumption and has shorter lifecycle that is connected to the increase of dynamics of changes in the last decades 20th century and the beginning of the 21 st century (Kodama, 1995;Strielkowski & Weyskrabova, 2014;Chernov, Dorokhova, & Dorokhov, 2016).…”
Section: Innovation In the Economic Literaturementioning
confidence: 99%